The legends of the Jews - Ginzberg, Louis (Jewish Publication Society of America, 1909)
I. Bible times and characters from the creation to Jacob -- II. Bible times and characters from Joseph to the exodus -- III. Bible times and characters from the exodus to the death of Moses -- IV. From Joshua to Esther. -- V. Notes to volumes I and II from the creation to the exodus -- VI. Notes to v. III and IV from Moses in the wilderness to Esther -- VII. Index, by Boaz Cohen